Knowledge gaps and research priorities for understanding the transmission of Mycobacterium tuberculosis and other airborne infections - Cegielski, J. Peter; Ahmedov, Sevim; Cheng, Jun; Dubick, Collin; Evans, Emily; Jensen, Paul A.; Kanchar, Avinash; Kansal, Anita Rani; Lin, Che-Chi; Liu, Yuhong; et al. (International Journal of Infection Control, 2025)
Despite 5 years of SARS-CoV-2 research, as well as decades of research on tuberculosis (TB), large gaps remain in understanding the transmission of airborne pathogens. Our aim was to delineate these gaps. Understanding them would enable evidence-based, practical efforts to reduce transmission. Building upon the 2017 Roadmap for TB Transmission Science, we interviewed experts in the field and identified six salient topics harboring holes in knowledge that impede prevention and control efforts. These include 1) fundamental elements of aerobiology, 2) detecting and measuring infectious respiratory particles directly in the air, 3) the infectiousness of asymptomatic TB (by extension, other lung infections) and 4) of calm tidal breathing – including their contributions to global epidemiology, 5) the role of ‘superspreading’ in disease incidence, and 6) the duration of infectiousness of highly drug-resistant TB treated with the newest, all-oral short-course regimens. Based on an extensive literature review, we update advances in science since 2017 and then summarize knowledge gaps and research priorities. Several recent systematic reviews all noted the relatively low quality of published research, so there is an overriding need for high-quality studies to provide evidence for national and international entities upon which to base recommendations, guidelines, and standards.